Analysis Porter's Five forces Model on Airbnb - Nurlansa, Osiany; Jati, Handaru (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2016)
This paper discusses about Airbnb. Airbnb is a company website that allows ordinary people to rent their residence as tourist accommodation. Anyone can rent rooms to suit their budget. The company established in 2008, and eight years later by a very rapid growth, the company reaches a turnover of millions of rooms per year. Airbnb analyzed using Porter's Five Forces Model. According to Porter, the competitive nature of the industry could be seen as a combination of top five strengths, namely Rivalry Among Existing Competitors, Threat of New Entrants, Threat of substitude Products or Services, Bargaining Power of Suppliers, Bargaining Power of Buyers. Data were processed using descriptive analysis. Analysis Airbnb terms of Porter's Five Forces Model concluded that from the fifth models of Porter, Rivalry Among Existing Competitors system, Threat of New Entrants, Threat of substitude Products or Services, Bargaining Power of Buyers robust system and one student Bargaining Power of Suppliers found to be very weakKeywords: porter's five forces model, airbnb, ecommerce